Processing Fly Ash and Bottom Ash (FABA) Waste into Briquettes as an Effort to Control Environmental Pollution at the West Sumbawa Steam Power Plant - Suripto; Saleh, Khalifah; Syukriadinata, Agung (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Student work practice has been carried out at West Sumbawa PLTU with the aim of transferring knowledge and work experience to students, especially regarding processing FABA waste into briquettes as an effort to reduce environmental pollution. Work practice was done using a direct practice method accompanied by a supervisor from the West Sumbawa PLTU and guided by lecturers from the Environmental Science Study Program Mataram University. The results show that after following the work practice, students know how to process FABA waste into briquettes, experiment with the use and examine briquette biomass. Making briquettes begins with grinding corn cobs, sawdust and FABA waste, then continues with sieving until a uniform flour particle size is obtained, continuing to mix with tapioca flour (as an adhesive) and water until a paste is obtained, molding until a certain shape and size is obtained and drying until the briquettes are as received (AR) and dry basis (DB). The experimental results show that the use of 50 to 100% briquettes can effectively replace coal with the PLTU load remaining stable at 6000 kW. Briquettes in AR condition contain 15.85% total water, 12.67% ash, 43.97% volatile matter, 27.53 fixed carbon, 0.10% total sulfur, and a rough calorific value of 4039 Kcal/kg. In DB conditions, briquettes contain 15.05% ash, 52.24% volatile matter, 32.71% fixed carbon, 0.11% total sulfur, and a calorific value of 4799 Kcal/kg. This information is important for evaluating fuel performance, energy efficiency and emissions from briquette application in steam power plants.